The role of human resource management in developing and implementing occupational health and safety policies and programs at Robi Axiata Limited - Hossain, Tamanna (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.